2021
DOI: 10.1016/j.neurad.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcome in childhood diffuse midline gliomas using magnetic resonance imaging based texture analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Using a software for MRI-based texture analysis on a single 2D image slice of DIPG tumors, one study of 32 patients suggested “homogeneous” texture may have worse outcome. 40 In this study, we conducted a 3D image analysis and applied a discovery-driven approach in search of significant computational features to create a prognostic machine learning model. Combined gadolinium-enhanced T1-MRI and T2-MRI outperformed either MRI sequence alone.…”
Section: Discussionmentioning
confidence: 99%
“…Using a software for MRI-based texture analysis on a single 2D image slice of DIPG tumors, one study of 32 patients suggested “homogeneous” texture may have worse outcome. 40 In this study, we conducted a 3D image analysis and applied a discovery-driven approach in search of significant computational features to create a prognostic machine learning model. Combined gadolinium-enhanced T1-MRI and T2-MRI outperformed either MRI sequence alone.…”
Section: Discussionmentioning
confidence: 99%
“…The best-characterized mutation is that of the NF2 gene, with other molecular mechanisms in the pediatric age group poorly characterized. Tumors in this age group are genetically distinct from their adult counterparts [78].…”
Section: Diagnosismentioning
confidence: 99%
“…They are rare in children, representing only 2-3% of pediatric CNS tumors [77]. Their incidence is markedly greater in syndromes like Neurofibromatosis 2, Schwannomatosis, Gorlin syndrome, and familial meningioma syndrome [77,78]. Exposure to irradiation in childhood predisposes to the development of meningiomas [77,78].…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
See 2 more Smart Citations